Characteristics of New Generation Teachers, According to the Teacher Production Curriculum of The Faculty of Education at the Universities of Lao PDR - DUANGPHACHANH, Phaivanh; SOUKHAVONG, Sithane; THALANGSY, Khamseng; KANYASAN , Kethsana; TAOCHANHXAY, Honglatda (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The objectives of study were: 1) to study the characteristics of the new generation teachers according to the teacher production curriculum of the Faculty of Education at the universities of Lao PDR; 2) to check the characteristics of the new generation teachers, according to the teacher production curriculum of the Faculty of Education at the universities of Lao PDR. The target groups of the study included; administrators, undergraduate teachers of the Faculty of Education at the universities of Lao PDR, and graduate’s user from teacher training colleges in Lao PDR with the total number of 83 participants. The research tools included a suitability and feasibility assessment forms with five-rating-scale and interview guideline form. The research method was applied the Delphi technique and the evaluation method by using the connoisseurship model, which consisted of two steps including; 1) analysis of documents for synthesis and drafting of components, and 2) checking the suitability and feasibility of the components of the indicators of the characteristics of the new generation teachers, according to the teacher production curriculum. Statistical techniques used in the analysis of the data obtained included median and interquartile range. The results were as follows: The characteristics of the composition and indicators of new generation teachers, according to the teacher production curriculum of the Faculty of Education at the universities of Lao PDR consisted of 6 components and 97 indicators including: The Political qualification component has 10 indicators, Competency in the teaching profession component has 23 indicators, Qualification in the teachers’ profession component has 19 indicators, Living plan component has 18 indicators, Protection of teachers’ dignity component has 15 indicators and the Ethical of the teachers’ profession component has 12 indicators.